(untitled) ("Temas Sociais" Journal, 2022)
Abstract: Care aimed at elderly people integrated in the home, aims to provide quality of life and well-being. This care is part of the care relationship, based on the dignity and rights of elderly people, so it is expected that formal care – geriatric agents- have training and qualifications aimed at the development and affirmation of the dignity of elderly people integrated in the home. This article addresses the profile of geriatric agents, as well as the training, skills and activities developed by these professionals in the care relationship. A qualitative approach is used, through documentary research, in order to broaden the debate on the importance of geriatric agents in the development of qualified care, drivers of the dignity of elderly people integrated in the home. The invisibility of these professionals are subject to in the development of care, insufficient training and low income are negative factors influencing the performance of these professionals.